OsHAK1, a High-Affinity Potassium Transporter, Positively Regulates Responses to Drought Stress in Rice - Chen, Guang; Liu, Chaolei; Gao, Zhenyu; Zhang, Yu; Jiang, Hongzhen; Zhu, Li; Ren, Deyong; Yu, Ling; Xu, Guohua; Qian, Qian (Frontiers in Plant Science, 2017)
Drought stress is one of severe environmental factors that greatly restrict plant distribution and crop production. Recently, we have reported that OsHAK1 played important roles in K acquisition and translocation in rice over low and high K concentration ranges. However, knowledge on the regulatory roles of OsHAK1 in osmotic/drought stresses is limited. Here, the transcript levels of OsHAK1 were found enriched transiently in roots and shoots by drought stress, consistent with the enhanced GUS activity under stress condition. With stunted growth under drought stress at both the vegetative and reproductive stages, OsHAK1 knockout mutants (KO) had lower resistance to drought conditions. Phenotypic analysis of OsHAK1 overexpression seedlings (Ox) demonstrated that they had better tolerance to drought stress than wild-type (WT). Compared with WT seedlings, overexpression of OsHAK1 had lower level of lipid peroxidation, higher activities of antioxidant enzymes (POX and CAT) and proline accumulation. Furthermore, qPCR analysis revealed that OsHAK1 acted as a positive regulator of drought tolerance by reinforcing the expression of two well-known rice channel genes (OsTPKb and OsAKT1) involved in K homeostasis and stress responses in transgenic plants under dehydration. Further investigation revealed that the expression levels of several stress-responsive genes were up-regulated in drought-tolerant OsHAK1-Ox plants. More importantly, the OsHAK1-Ox plants showed significantly enhanced drought tolerance at reproductive stage, which increased grain yield by 35% over controls under drought conditions, yet exhibited no significant difference under normal growth conditions. Therefore, OsHAK1 is believed to be applied in molecular breeding for improvement of drought stress tolerance in rice.